ACTUATOR AND SENSOR FAULT COMPENSATION USING PROPORTIONAL-PROPORTIONAL INTEGRAL OBSERVER FOR FUZZY TRACKING CONTROL OF PENDULUM-CART SYSTEM (Jurnal Teknologi (Sciences & Engineering), 2023)
The pendulum-cart system is a popular system plant as a case study in nonlinear control design and implementation. The controllability and system performance can be influenced by the effectivity of the actuator and sensor. However, actuator and sensor fault sometimes is inevitable and can be occurred during operation. This paper considers fault-tolerant control (FTC) to minimize the actuator and sensor fault. The control objective is to track the sinusoidal reference position of the cart while the pendulum is maintained upright in which the faulty actuator and sensor occurred. Takagi-Sugeno (T-S) fuzzy tracking control is designed based on a compensator scheme where the Proportional-Proportional Integral Observer (PPIO) is utilized for this scheme. The Linear Matrix Inequalities (LMIs) are used to calculate the controller and observer gains. The performance of the proposed controller is verified through simulation and experimental validation. The effectiveness of FTC in the case of actuator and sensor fault is given. The system responses for the compensated and uncompensated controllers (to track the reference signal) are compared. In the case of a sensor fault, only the compensated controller can converge to the reference signal. However, in the case of actuated fault, both compensated and uncompensated controllers converge to the reference signal but the error of the compensated controller is better than the other one.